The Historical Development of the Sa'adatuddarain Educational Foundation in Mampang Prapatan: A Historical Study of Its Origins, Development, and Contributions to Education and Society - Y. Yusron; Abdul Rosyid Teguhdin Hamid (Golden Ratio of Data in Summary, 2026)
This study examines the historical development of the Sa'adatuddarain Educational Foundation, an Islamic educational institution in Mampang Prapatan, South Jakarta, that has operated for more than six decades. Using a qualitative historical approach, the research applies heuristics, source criticism, interpretation, and historiography to institutional documents, official education data, interviews, media reports, and scholarly literature. The findings show that four religious scholars and community leaders established the foundation in the 1960s. It subsequently developed from a religious elementary institution into an integrated educational system extending from kindergarten to Islamic senior high school. Enrollment grew from approximately 1,400 students in 2011/2012 to 2,000 in 2019, while its alumni exceeded 10,000. The foundation also supports orphans and disadvantaged communities, distributes sacrificial meat, and collaborates with government institutions on teacher assistance programs. Its continuity reflects effective family-based leadership succession, scholarly networks, institutional adaptability, sustained religious commitment, and enduring concern for community welfare and education.